Effects of phosphate and two-stage sous-vide cooking on textural properties of the beef semitendinosus - Ruslan, Nurul Nazirah; Tang, John Yew Huat; Huda, Nurul; Ismail-Fitry, Mohammad Rashedi; Ishamri, Ismail (Korean Society for Food Science of Animal Resources, 2023)
Comparing the effects of sodium tripolyphosphate (STPP) concentrations of 0.2 and 0.4 on beef semitendinosus is the objective of the current investigation. The samples were cooked at varied temperatures (45+60„ƒ and 45+70„ƒ) and times (1.5+1.5 h and 3+3 h) using staged cooking. The colour properties, cooking loss, water retention, shear force, water-holding capacity, sarcoplasmic, and myofibrillar solubility, and total collagen were investigated. The cooking time and temperature affected the water-holding capacity, cooking loss, CIE L*, CIE a*, CIE b*, myofibrillar, and sarcoplasmic solubility, with lower temperature and short time having the lower detrimental effect. However, the significant effect can be intensified after the addition of STPP with higher water-holding capacity and tender meat obtained with 0.4 phosphate concentration at any cooking conditions. The STPP lowered the collagen content and increased the protein solubility of myofibrillar and sarcoplasmic, which this degradation is used as a good indicator of tenderness.